PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK EDUKASI DIGITAL UNTUK MENINGKATKAN MINAT BACA SISWA KELAS IV SEKOLAH DASAR: R&D - Mardia, Dwigia; Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital education comic-based learning media and examine its feasibility, practicality, and effectiveness in improving fourth-grad elementary school students’ reading interest. This research employed the Research and Development (R&D) method using the ADDIE model. The subjects consisted of 36 students from two elementary schools. Date were collected through expert validation sheets, practicality questionnaires, and pretest-posstest instrument. The results showed that the developed media was higly valid (89,33%), very practical (95%-96%), and highly effective, with N-Gain scores of 93,28% and 95,96% categorized as high. The fidings indicate that digital comic-based learning media significantly improve students’ reading interest and engagement. Therefore, this media can be recommedded as an innovative learning solution in elementary education